THE EFFECT OF L- ARGININE ON OXIDATIVE STRESS AND MICROALBUMINURIA IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AND CHRONIC KIDNEY DISEASE - Martynyuk, L. P.; Vons, L. Z.; Ruzhytska, O. O. (International Journal of Medicine and Medical Research, 2017)
Background. One of the severest complications of diabetes is diabetic kidney disease (DKD). Microalbuminuria (MAU) is one of the first signals of DKD and an important pathogenetic mechanism of disease progression. With diabetes dramatically antioxidant properties worsen. Objective. The aim was to investigate the effect of L-arginine on oxidative stress parameters and microalbuminuria in type 2 diabetes mellitus and chronic kidney disease patients. Methods. Total of 57 patients with type 2 diabetes mellitus and chronic kidney disease and 30 healthy subjects (control group) were included in the study. The patients were divided into 2 congruent groups. The 1-st group of patients (n=33), in addition to standard therapy, received L-arginine 4.2 g intravenously for 5 days, after that they took it 1,0 g orally three times a day during meals for 1 month. The second group of patients (n=24) received a standard therapy. The concentration of lipid peroxidation products was measured by a spectrophotometric method. The determination of MAU was carried out in morning portion of urine immunological semiquantitative using test strips. Results. Significant improvement in indexes of lipid peroxidation was observed in both groups after therapy (p˂0.01), but in patients treated with L-arginine it was more expressed (p˂0,01). The standard therapy did not significantly affect the level of MAU (p˃0,05). The patients treated with L-Arginine, showed a significant reduction in MAU (p˂0.01). Conclusions. The usage of L-arginine facilitates the correction of lipid peroxidation processes and reduces the severity of microalbuminuria in patients with diabetic kidney disease that slowing its progression.